SMAD 3, Integrin and VEGF Expression in a Periodontal Ligament During Orthodontic Tooth Movement Induced by Hyperbaric Oxygen Therapy and Stichopus hermanii - Prameswari N; Brahmanta A; Sucahyo B (Clinical, Cosmetic and Investigational Dentistry, 2022)
Noengki Prameswari,1,2 Arya Brahmanta,1,2 Bambang Sucahyo1,2 1Orthodontic Laboratory, Hang Tuah University, Surabaya, Indonesia; 2Nala Husada Dental Hospital, Hang Tuah University, Surabaya, IndonesiaCorrespondence: Noengki Prameswari, Orthodontic Laboratory, Hang Tuah University, Surabaya, Indonesia, Tel +62-81332410722, Email noengki.prameswari@hangtuah.ac.idPurpose: The aim of this study is to analyze SMAD 3, integrin and VEGF expressions in the periodontal ligament during orthodontic tooth movement induced by hyperbaric oxygen therapy and Stichopus hermanii.Materials and Methods: Thirty Cavia cobaya were divided into 5 groups, namely, a normal control group (KN) without installation of helical springs or administration of HBOT and Stichopus hermanii gel. The negative control K(-) had helical spring without administration of HBOT and Stichopus hermanii gel for 14 days, while P1 had helical spring for 14 days then on day 3– 14, Stichopus hermanii gel was added. Also, the helical spring was installed in P2 for 14 days then on day 8– 14, HBOT 2.4 ATA was added 3 × 30 minutes a day, while P3 had helical spring for 14 days then on day 3– 14, the gel was applied, and on day 8– 14, HBOT 2.4 ATA was administered 3 × 30 minutes a day. Furthermore, SMAD3, integrin, and VEGF expressions were examined using immunohistochemical staining.Results: SMAD3, integrins, and VEGF expressions showed significant differences within the groups. The combination of HBOT and Stichopus hermanii increased the expression of SMAD3 and VEGF compared to the single administration of Stichopus hermanii. The combination treatment also decreased integrin expression compared to a single HBOT administration.Conclusion: The combination of HBOT and Stichopus hermanii increases the expression of SMAD3, integrins, and VEGF compared to control but did not show significant differences compared to single HBOT treatment.Keywords: collagen, vascularization, periodontal ligament fibers, orthodontic treatment